MEASURING VALUE IN THE VIDEO GAMES CONTEXT - Voulgaris, Aristeidis (2012)
The video games global market has been enjoying massive growth over the past years. More people from diverse demographic backgrounds are gradually becoming involved to gaming and it is slowly becoming a common activity for many people. Using the framework developed by Smith and Colgate (2007) this paper attempts to explore the structure of customer value in the video games context and develop an understanding regarding how value varies across different consumer segments.